Management Education: Unfulfilled Promises and New Prospects - THOMAS, Howard (Institutional Knowledge at Singapore Management University, 2013)
At the beginning of his study Ivy and Industry: Business and the Making of the American University, 1880-1980, Christopher Newfield writes, “the university is a corporate and a utopian environment at the same time, and has been the central site for considering the possibility that once modernity had irreversibly delivered a world of organisations, the corporate might be made utopian, and the utopian might be post-corporate” (2003, pp. 4-5). As a one-sentence history of the modern university, and not just the modern American university, this summary contains much of the promise and much of contention that fuels the essays in this special issue. Too often management education has been seen as a mere antagonist in this history, emblematic of only one side, the corporate university. Thinking of the modern university as a site for negotiating these corporate and utopian impulses, but even more, as a site of imagining a reconciliation, even a transformation of these impulses allows us to put management education at the heart of this project. Where better to situate this negotiation and to place these hopes than in the midst of these two words, embodying as they do the coming together of the corporate and the utopian personality of the university. Management is at base the recognition that, as Newfield says, our modern condition has “irreversibly delivered a world of organisations”. While on the other hand education is fundamentally the conviction that humans are capable of growth and development. Management education therefore ought to be an even more concise summary of Newfield's own summary. Moreover these two words ought to signal the potential of this communion of the utopic and the corporate. Indeed, the essays in this special issue all operate in one way or another at the nexus of this possibility. They also do so with a sense of urgency. There is a sentiment running throughout these essays that now is the time to get management education right. The rising tide of the global knowledge economy is lifting higher education but it is also taking the university into dangerous waters.